Comparative theoretical-experimental study applied to the analysis of the gene expression of DNA forms in arthropods and mammalian cells infected by Dengue Vírus (Research, Society and Development, 2020)
Objective: A study with a theoretical-experimental approach applied to the gene expression of DENV DNA forms in mammalian cells, compared to the presence of fragments originating from viral RNA described in the literature in arthropod cells, experimentally infected by DENV. Methodology: This is a bilateral study, of a theoretical-experimental nature, with a primary intervention basis, carried out in vitro, under a comparative technical approach. Laboratory techniques for gene expression by conventional PCR, verification procedures for analysis and literature data records were obtained and processed at the Viral Biogenesis Laboratory, linked to the Arbovirology and Hemorrhagic Fevers Sector of the Evandro Chagas Institute.  Results: Experimental analysis indicated the presence of DENV-4 DNA forms in cells persistently infected by inoculation at 72 hpi. As a comparative function, C6/36 cells presented viral DNA sequences incorporated in regions of LTR retrotransposons, thus allowing to suggest that most integration events are mediated by reverse transcriptases derived from retrotransposons. Conclusion: Given the results demonstrated, it becomes evident the need for studies that characterize the ability of viral RNA to be converted into DNA forms, as well as the influence of this characteristic on the permanence of these fragments after infection, to which proteins these genes belongs, how these genes modify and interact in viral replication and the relationship of pathogenicity and tropism associated with post-mutation protein molecular plasticity, during viral replication.